Emerging role of carbon ion radiotherapy in reirradiation of recurrent head and neck cancers: what have we achieved so far? - Bhattacharyya, Tapesh; Koto, Masashi; Windisch, Paul; Ikawa, Hiroaki; Hagiwara, Yasuhito; Tsuji, Hiroshi; Adeberg, Sebastian (Frontiers in oncology, 2022)
Administering reirradiation for the treatment of recurrent head and neck cancers is extremely challenging. These tumors are hypoxic and radioresistant and require escalated radiation doses for adequate control. The obstacle to delivering this escalated dose of radiation to the target is its proximity to critical organs at risk (OARs) and possible development of consequent severe late toxicities. With the emergence of highly sophisticated technologies, intensity-modulated radiotherapy (IMRT) and stereotactic body radiotherapy have shown promising outcomes. Proton beam radiotherapy has been used for locally recurrent head and neck cancers because of its excellent physical dose distribution, exploring sharp Bragg peak properties with negligible entrance and exit doses. To further improve these results, carbon ion radiotherapy (CIRT) has been explored in several countries across Europe and Asia because of its favorable physical properties with minimal entrance and exit doses, sharper lateral penumbra, and much higher and variable relative biological efficacy, which cannot be currently achieved with any other form of radiation. Few studies have described the role of CIRT in recurrent head and neck cancers. In this article, we have discussed the different aspects of carbon ions in reirradiation of recurrent head and neck cancers, including European and Asian experiences, different dose schedules, dose constraints of OARs, outcomes, and toxicities, and a brief comparison with proton beam radiotherapy and IMRT.
Gesehen am 08.07.2022